In vitro efficacy of five pediatric toothpastes in the inhibition of Streptococcus mutans ATCC 25175. - José Miñano; María V. Espinoza (Universidad de Concepción., 2020)
The present in vitro study compared the inhibitory action of five pediatric toothpastes against Streptococcus mutans ATCC 25175. Materials and Methods: Cross-sectional, comparative and experimental study. The microorganism Streptococcus mutans ATCC 25175 was inoculated onto solid culture medium of Müeller-Hinton supplemented with blood, then the plates were inoculated with five pediatric toothpastes: Oral B Stages, Colgate Smiles, Aquafresh My Little Teeth, Dentito and Denture Kids. Samples were incubated at 37°C for 48 hours. Subsequently the inhibition halos were measured; the experiment was repeated 20 times for each sample. Statistical analysis was performed with ANOVA complemented with Tukey's test. Results: Oral B Stages yielded a mean inhibitory halo of 23.2mm, Colgate Smiles an average of 21.7mm, Aquafresh My Little Teeth of 13.6mm, Dentito of 18.5mm, and Denture Kids a mean of 23.0mm. When performing the ANOVA test, it was found that there was a significant difference in the inhibitory action of pediatric toothpastes (p<0.005) and when using Tukey's multiple comparison test, Oral B and Denture Kids presented similar inhibitory action. Conclusion: All toothpastes presented inhibitory action against Streptococcus mutans ATCC 25175. A significant difference between their effectiveness was observed. Oral B Stages showed the greatest degree of inhibition.